An online review on customer satisfaction of mid-to-high-end health and wellness hotels in China - Xiaolin, Chen; Marzuki, Azizan (Edelweiss Applied Science and Technology, 2024)
The rapid development of information technology has enabled the collection of online review data, which provides a more precise representation of hotel guest satisfaction. It is crucial to investigate the factors that impact hotel guest satisfaction as identified through online review content. This study will examine relevant scholarly literature on online reviews and concentrate on 50 mid-to-high-end health and wellness hotels in China. Python is utilized to crawl the online review database, and a comprehensive analysis is conducted on the semantic keywords and categories present in customer online review statements. Service, traffic, catering, and other variables are identified as determinants of customer satisfaction in mid-to-high-end health and wellness hotels through factor analysis. This article will propose specific measures and recommendations to improve customer satisfaction in health and wellness hotels, attract more customers, and contribute to the sustainable development of the industry.